Pengaruh Literasi Pajak, Kesadaran Pajak, dan Sanksi Pajak terhadap Kepatuhan Wajib Pajak UMKM di Kabupaten Bengkalis - Tiara, Siti; Eryana, Eryana (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study aims to analyze the influence of tax literacy, tax awareness, and tax sanctions on the tax compliance of Micro, Small, and Medium Enterprises (MSMEs) in Bengkalis Regency. A quantitative approach was applied using a survey method, with questionnaires distributed to 100 MSME taxpayers registered at the Bengkalis Tax Service Office. The data were analyzed using multiple linear regression with the assistance of SPSS version 26. The results indicate that tax literacy, tax awareness, and tax sanctions have a positive and significant effect on taxpayer compliance. The Adjusted R² value of 0.691 shows that 69.1% of the variation in tax compliance is explained by the three independent variables. Among them, tax literacy is the most dominant factor influencing compliance behavior. These findings emphasize that improving MSME tax compliance requires an integrated approach through enhanced literacy, awareness development, and the consistent implementation of fair tax sanctions. This research is expected to serve as a policy reference for local governments and the Directorate General of Taxes in designing effective tax compliance strategies based on MSME empowerment.